High temperature plasticity at twin boundary in Al: An in-situ TEM perspective. (1st June 2023) - Larranaga, M.; Lartigue-Korinek, S.; Legros, M.; Combe, N.; Mompiou, F.
Abstract: Coherent twin boundaries are of special importance in structural materials due to their strengthening ability by impeding dislocation motion while maintaining possible glide along their plane. Interactions of lattice dislocations with twin boundaries have been extensively studied experimentally and numerically but relaxation and deformation processes at high temperature are not fully understood. The reason is related to complex mechanisms of dislocation decompositions into disconnections, their further motion and possible reactions. Moreover, as in shear-coupled grain boundary (GB) mechanisms, motion of disconnections in the interface plane is expected to lead to twin motion perpendicular to its plane. Here, shear-coupled motion of a coherent twin in pure Al is explored during in situ straining in a transmission electron microscope (TEM) in a favorable geometrical configuration. Surprisingly, the twin boundary does not couple to shear but slightly migrates by propagating nanoscale incoherent facets. Although, disconnections of Burgers vector 1 / 6 〈 112 〉 have been extensively observed moving in the interface plane, their motion did not lead to migration as expected but presumably to GB sliding. This was interpreted by the motion of disconnections with opposite single and double steps in the [ 111 ] direction. Extensive dislocation/GB interactions were observed and reactions following absorption are interpreted by contrast analysis and motion observations. Incoming dislocations do not always decompose but often react with the GB disconnection microstructure which may lead to intergranular motions or dislocation emissions in the adjacent grain. As these processes usually involve disconnection climb in the interface plane, direct transmission, i.e. spatially and temporally correlated absorption/emission processes, is not observed as revealed by large scale observations. Finally, the internal disconnection microstructure of the twin boundary often forms networks which although flexible are found to slow down intergranular plasticity. Such networks should strongly control stress induced mechanisms in realistic GBs. Graphical abstract: